Habilitation, health, and agency a framework for basic justice - Becker, Lawrence C. (New York ; Oxford : Oxford University Press, 2012)
Lawrence C. Becker introduces an unconventional set of background ideas for future philosophical work on normative theories of basic justice. The organizing concept is habilitation - the process of equipping a person or thing with functional abilities or capacities.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Includes bibliographical references and index.
Keywords: Political science -- Philosophy; Justice; Health; Medical ethics